Melatonergic Drugs for Therapeutic Use in Insomnia and Sleep Disturbances of Mood Disorders - Srinivasan, Venkatramanujam; Zakaria, Rahimah; Othman, Zahiruddin; Brzezinski, Amnon; Prasad, Atul; Brown, Gregory M. (Bentham Science Publishers, 2012)
Insomnia is common among elderly people and nearly 30 to 40% of the adult population also suffer from insomnia. Pharmacological treatment of insomnia include the use of benzodiazepine and non-benzodiazepine drugs like zolpidem, zaleplon,Zopiclone. Although these drugs improve sleep ,their usage is also associated with number of adverse effects, Melatonin ,the hormone secreted by the pineal gland of all animals and human beings has been used for treatment of insomnias,since the timing of its secretion in humans as well as in most of the animals coincides with the increase of nocturnal sleep propensity.Because of its short half life,melatonin slow release preparations were introduced for treatment of insomnia. Recently ramelteon ,a selective MT1,MT2 receptor agonist with greater efficacy of action in treating insomnia has been used clinically and has been found effective in improving sleep quality ,sleep efficacy and also in reducing the sleep onset time when compared to melatonin or slow melatonin preparations.The mechanism of action of ramelteon in improving sleep is discussed in the paper. Another melatonergic drug agomelatine besides acting on MT1/MT2 receptors also displays 5-HT2c antagonism and this drug has been found effective as a novel antidepressant for treating major depressive disorders.Agomelatine besides causing remission of depressive symptoms also improves sleep quality and efficiency. Other antidepressants depressants that are in clinical use today do not improve sleep. There are other melatonergic drugs like tasimelteon ,6-chloromelatonin.But ramelteon and agomelatine deserve special attention for treatment of insomnia and sleep disturbances associated with depressive disorders and have promising role for treatment of sleep disorders.